The Role of Transient Receptor Potential Channel 6 Channels in the Pulmonary Vasculature - Malczyk, Monika; Erb, Alexandra; Veith, Christine; Ghofrani, Hossein Ardeschir; Schermuly, Ralph T.; Gudermann, Thomas; Dietrich, Alexander; Weissmann, Norbert; Sydykov, Akylbek (Frontiers in Immunology, 2017)
Transient receptor potential channel 6 (TRPC6) is a Ca2+-permeable non-selective cation channel that is widely expressed in the heart, lung and vascular tissues. The use of TRPC6-deficient (“knockout”) mice has provided important insights into the role of TRPC6 in normal physiology and disease states of the pulmonary vasculature. Evidence indicates that TRPC6 is a key regulator of acute hypoxic pulmonary vasoconstriction. Moreover, several studies implicated TRPC6 in the pathogenesis of pulmonary hypertension. Furthermore, a unique genetic variation in the TRPC6 gene promoter has been identified which might link the inflammatory response to the upregulation of TRPC6 expression and ultimate development of pulmonary vascular abnormalities in idiopathic pulmonary arterial hypertension. Additionally, TRPC6 is critically involved in the regulation of pulmonary vascular permeability and lung edema formation during endotoxin or ischemia/reperfusion-induced acute lung injury. In this review, we will summarize latest findings on the role of TRPC6 in the pulmonary vasculature.